Influence of in situ ettringite formation on the rheological properties of quartz suspensions - Kißling, Patrick A.; Link, Julian; Heinemann, Melanie; Lübkemann-Warwas, Franziska; Rieck genannt Best, Felix; Sowoidnich, Thomas; Mundstock, Alexander; Ludwig, Horst-Michael; Haist, Michael; Bigall, Nadja C. (Construction & building materials, 2023)
•Simplified up-scalable synthesis route of in situ ettringite in an inert matrix.•Impact of nano-granular ettringite on bulk rheology of a model suspension.•Correlation of particle’s specific surface area with rheological properties.•Varying impact of ettringite particles’ fineness on yield stress and plastic viscosity. Cement suspensions are subject to hydration processes causing dissolution of cement clinker, precipitation of hydration products and changes in the ion content of the carrier liquid. These mechanisms take place in parallel and control the workability of cement suspensions. The precipitation of nano-granular ettringite is currently believed to be one of the key influencing factors for rheological properties of fresh cement suspensions. In order to quantify the effect of ettringite precipitation from other precipitation or dissolution processes onto the rheological behaviour, a model suspension consisting of quartz powder and in situ formed ettringite is used, enabled by implementing a new upscalable synthesis route of ettringite. The quantity of formed ettringite in the model suspension is varied and derived qualitatively from X-ray diffraction as well as quantitatively from inductively coupled plasma optical emission spectrometry and thermogravimetric analysis. The influence of the ettringite content on the rheological properties is determined and linked to the specific surface of the formed ettringite particles. This allows a quantification of the controlling mechanism of ettringite and the dependency of these mechanisms on particle properties. The correlation of the results to a reference suspension without ettringite verifies the statement of influence.